2011
DOI: 10.1007/s10266-011-0005-6
|View full text |Cite
|
Sign up to set email alerts
|

Condition of depressive symptoms among Japanese dental students

Abstract: The Zung Self-Rating Depression Scale (SDS) is generally used to screen for the presence of depression. The purpose of this study was to investigate scores on the SDS, Japanese version, in undergraduates at Tsurumi University School of Dental Medicine in Yokohama, Japan. A total of 2,197 dental students completed the SDS from 2006 through 2008. The investigation took place each year over a 3-week period from June to July. When investigating, the Institutional Review Board at Tsurumi University approved the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 20 publications
4
33
0
2
Order By: Relevance
“…Little attention has been paid to depression among dental students. The results of studies conducted on clinical years ranged between 2.8 and 15%, and between 7.4 and 14% on preclinical years (9,13,14), using different instruments and cutoff values to screen for depression. Considering gender, the abovementioned authors reported that more female than male dental students showed positive results for depression in clinical and preclinical years, except for Takayama (2), who found no gender differences among students in preclinical years.…”
Section: Introductionmentioning
confidence: 99%
“…Little attention has been paid to depression among dental students. The results of studies conducted on clinical years ranged between 2.8 and 15%, and between 7.4 and 14% on preclinical years (9,13,14), using different instruments and cutoff values to screen for depression. Considering gender, the abovementioned authors reported that more female than male dental students showed positive results for depression in clinical and preclinical years, except for Takayama (2), who found no gender differences among students in preclinical years.…”
Section: Introductionmentioning
confidence: 99%
“…Especificamente quanto à sintoma depressivos, encontram-se estimativas que vão de 8,7% a 37,4% (Vázquez & Blanco, 2008;Parrish, Cohen & Laurenceau, 2011;Takayama, Miura, Miura, Ono, Ohkubo, 2011). Estimulado pela afirmação de que estudantes universitários são particularmente vulneráveis à depressão (Merritt, Price, Mollison & Geddes, 2007), vê-se respeitável a busca de pesquisas que avaliam a sintomatologia depressiva em universitários.…”
Section: Revista De Psicologia Daunclassified
“…U studiji sprovedenoj među studentima u Limi 31,2% pokazalo je simptome depresivnosti na Zungovoj skali samoprocene (11). Slična prevalenca (11-37%) je i u zemljama Istočne Azije (16,(37)(38)(39), mada je stopa depresije u opštoj populaciji u azijskim zemljama nešto niža nego u zapadnim zemljama (40,41).…”
Section: Učestalost Depresivnostiunclassified